(untitled) - Robin, Harry (New York, 1992)
Examines the efforts of scholars and science aficionados alike to conceive, document, describe, classify, order, and analyze natural phenomena with the aid of illustrations as varied as their interests and methods. Author Harry Robin has assembled scores of intriguing images, including an ancient Chinese pulse chart; stroboscopic photographs, PET scans, and computer graphics, a detailed rendering of fossil layers in a mountain sliced by glacial erosion, astronomical drawings from the tomb of an Egyptian pharaoh, and diagrams of sixteenth-century methods for treating crossed eyes and an injured spine. Each illustration is accompanied by an insightful, accessible commentary, in which Robin explains the image and its context.
Keywords: Science,Khoa học; Graphic methods,Phương pháp đồ họa